2018
DOI: 10.12691/ajmcr-6-9-2
|View full text |Cite
|
Sign up to set email alerts
|

Brugada Pattern in Diabetic Ketoacidosis: A Case Report and Scoping Study

Abstract: Brugada syndrome is a rare cardiac arrhythmia which is associated with right bundle branch block pattern (RBBB) and ST-segment elevation in right precordial leads. SCNA5 mutation is the most common genetic abnormality associated with Brugada syndrome. Brugada pattern not related to genetic mutations has been previously reported in the setting of fever, metabolic conditions, lithium use, marijuana and cocaine abuse, ischemia and pulmonary embolism, myocardial and pericardial diseases. Multiple isolated cases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 47 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Ion channel dysfunction has been associated with diabetes mellitus (DM), leading to the development of a heart disorder called diabetic cardiomyopathy (179,180), characterized by contractile dysfunction, abnormal cardiac electrical activity, mitochondrial dysfunction, arrhythmia, and sudden cardiac death (159,160). Several patients affected by DM have been reported to exhibit the BrS ECG pattern, whether it was considered "true BrS" or a "BrS phenocopy" (104,(181)(182)(183)(184), although a difference between "true BrS" and "BrS phenocopy" may not actually exist (41). A case report described a 16-yearold boy affected by DM and a mutation in the GPD1L gene who died suddenly during the night (185).…”
Section: Brugada Syndrome and Diabetesmentioning
confidence: 99%
“…Ion channel dysfunction has been associated with diabetes mellitus (DM), leading to the development of a heart disorder called diabetic cardiomyopathy (179,180), characterized by contractile dysfunction, abnormal cardiac electrical activity, mitochondrial dysfunction, arrhythmia, and sudden cardiac death (159,160). Several patients affected by DM have been reported to exhibit the BrS ECG pattern, whether it was considered "true BrS" or a "BrS phenocopy" (104,(181)(182)(183)(184), although a difference between "true BrS" and "BrS phenocopy" may not actually exist (41). A case report described a 16-yearold boy affected by DM and a mutation in the GPD1L gene who died suddenly during the night (185).…”
Section: Brugada Syndrome and Diabetesmentioning
confidence: 99%
“…In this case, severe hyperkalemia and acidosis secondary to diabetic ketoacidosis were likely the precipitating factors causing the BrP findings. The mechanism of BrP in patients with DKA is not fully understood but is proposed to be related to hyperkalemia and acidosis inactivating cardiac sodium ion channels by decreasing the resting membrane potential [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first indication of this connection between blood glucose and cardiac events in Brugada syndrome is a report from the Thai ministry of Public Health in 1990. They found an association between Brugada syndrome patients consuming a large carbohydrate-heavy meal the night they passed away in their sleep [ 8 ]. This association was further investigated in Nogami et al who found the accentuation of ST-segment in high-risk Brugada syndrome patients following infusion of glucose or glucose and insulin solution, even with little to no isoelectric separation between the Brugada syndrome patients and controls [ 9 ].…”
Section: Discussionmentioning
confidence: 99%